2017
DOI: 10.17116/jnevro20171174186-91
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological neuroprotection in stroke in clinical practice: new perspectives

Abstract: Despite recent advances in acute stroke care, clinical armamentarium against stroke remains limited. Furthermore, highly effective approaches to stroke treatment, such as systemic reperfusion and mechanical thrombectomy, cannot be performed in the majority of patients. Neuroprotective strategies, i.e. prevention of irreversible cell damage due to the ischemia, may improve stroke outcomes. However, only few pharmacological agents demonstrated clinical efficacy. Citicoline is an endogenous mononucleotide with ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 30 publications
0
3
0
1
Order By: Relevance
“…Among these, Citicoline (cytidine-5’-diphosphocholine) is an endogenous compound that can be administered exogenously with proven neuroenhancement effects in many brain and ocular diseases characterised by hypoxia and ischemia [28], such as stroke [29,30], brain trauma [31], Parkinson’s disease [32,33], Alzheimer’s disease [29,34,35], glaucoma [3640], and NAION [41,42].…”
Section: Introductionmentioning
confidence: 99%
“…Among these, Citicoline (cytidine-5’-diphosphocholine) is an endogenous compound that can be administered exogenously with proven neuroenhancement effects in many brain and ocular diseases characterised by hypoxia and ischemia [28], such as stroke [29,30], brain trauma [31], Parkinson’s disease [32,33], Alzheimer’s disease [29,34,35], glaucoma [3640], and NAION [41,42].…”
Section: Introductionmentioning
confidence: 99%
“…Kobets [ 578 ] confirms the efficacy of citicoline in the management of acute ischaemic stroke. Sergeev et al [ 579 ] concluded that maximal effect of citicoline is seen when it is administered as soon as possible after stroke onset in patients who are not eligible for reperfusion therapy. Seifaddini et al [ 580 ] concluded that prescription of citicoline for treatment of acute ischemic stroke is associated with hemodynamic changes in cerebral arteries and that this finding can be one of the citicoline’s mechanisms of action in ischemic stroke process.…”
Section: Clinical Experiencementioning
confidence: 99%
“…Kobets [ 578 ] confirma la eficacia de la citicolina en el manejo del accidente cerebrovascular isquémico agudo. Sergeev et al [ 579 ] concluyeron que el efecto máximo de la citicolina se observa cuando se administra lo antes posible después del inicio del accidente cerebrovascular en pacientes que no son elegibles para la terapia de reperfusión. Seifaddini et al [ 580 ] concluyeron que la prescripción de citicolina para el tratamiento del accidente cerebrovascular isquémico agudo está asociada con cambios hemodinámicos en las arterias cerebrales y que este hallazgo puede ser uno de los mecanismos de acción de la citicolina en el proceso de accidente cerebrovascular isquémico.…”
Section: Experiencia Clínicaunclassified
“…[ 22 ] Early administration of citicoline is recommended for patients unsuitable for reperfusion therapies. [ 23 ] In a randomized clinical trial administering citicoline to acute stroke patients, both hemorrhagic and ischemic, the citicoline group showed statistically significant lower disease severity than the control group after Day 90, particularly in ischemic patients,[ 24 ] prompting long-term citicoline administration.…”
Section: Introductionmentioning
confidence: 99%